2017
DOI: 10.1073/pnas.1610630114
|View full text |Cite
|
Sign up to set email alerts
|

A distinct subset of plasmacytoid dendritic cells induces activation and differentiation of B and T lymphocytes

Abstract: Plasmacytoid dendritic cells (pDCs) are known mainly for their secretion of type I IFN upon viral encounter. We describe a CD2 hi CD5 + CD81 + pDC subset, distinguished by prominent dendrites and a mature phenotype, in human blood, bone marrow, and tonsil, which can be generated from CD34 + progenitors. These CD2 hi CD5 + CD81 + cells express classical pDC markers, as well as the toll-like receptors that enable conventional pDCs to respond to viral infection. However, their gene expression profile is distinct,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 52 publications
4
99
0
Order By: Relevance
“…A re‐interpretation of these results would suggest that in vitro culture causes short‐lived mature pDC to decline, while differentiating myeloid cDC come to dominate the preparation. This conclusion had been anticipated to a degree by a number of reports describing subsets of CD123 + pDC marked by CD2 or CD56 that show myeloid DC characteristics of inferior type I interferon production, higher interleukin‐12 (IL‐12) production and greater allo‐stimulatory capacity …”
Section: Human Pre‐dendritic Cells and Axl+siglec6+ DCmentioning
confidence: 93%
See 1 more Smart Citation
“…A re‐interpretation of these results would suggest that in vitro culture causes short‐lived mature pDC to decline, while differentiating myeloid cDC come to dominate the preparation. This conclusion had been anticipated to a degree by a number of reports describing subsets of CD123 + pDC marked by CD2 or CD56 that show myeloid DC characteristics of inferior type I interferon production, higher interleukin‐12 (IL‐12) production and greater allo‐stimulatory capacity …”
Section: Human Pre‐dendritic Cells and Axl+siglec6+ DCmentioning
confidence: 93%
“…Transciptional profiling has also added the markers FAM129C, CUX2 and GZMB . Several recent papers have described a small subset of CD123 + pDC that express CD2 + , CD56 + or CD5 . These cells have a distinct gene expression pattern that overlaps with myeloid cDC and are now known to contain AXL + SIGLEC 6 + myeloid pre‐cDC as described above.…”
Section: Plasmacytoid Dendritic Cellsmentioning
confidence: 99%
“…Recently, it has been reported that human cDC2 in tonsils, lymph nodes (LN), and blood as well as skin Langerhans and dermal DCs and blood pDCs can be further subdivided into CD5 positive and negative subpopulations, demonstrating for the first time that some human DCs express CD5 . In this context, it has been observed that CD5 is also expressed in DCs in mice (Burgueño‐Bucio et al., unpublished data).…”
Section: Cd5 General Remarksmentioning
confidence: 96%
“…Another study has demonstrated that skin Langerhans and dermal DCs can also be subdivided based on CD5 expression: CD5+ skin DCs are more potent at inducing CD8+ and CD4+ T cell proliferation and increased production of granzyme B, IFN‐γ, and TNF‐α in CD8+ T cells and IL‐22 in CD4+ T cells . Finally, it has also been proven that pDCs in blood can be further subdivided in CD5 positive and negative subpopulations and that CD5+ pDCs present a more mature phenotype, but that they do not produce great amounts of type I IFNs; nevertheless, they induce greater proliferation of B cells and induce plasma cell and Treg differentiation . However, the functional relevance of CD5 in these different subpopulations of DCs needs to be further investigated.…”
Section: Role Of Cd5 In Dendritic Cell Biologymentioning
confidence: 99%
“…Whether the CD123 hi CD33 + C-D45RA + precursors identified in that study can be differentiated into CD5 + DCs was not tested; however, they were reported to express CD5. Two additional studies identified CD123 + DC populations in peripheral blood that are within the pDC gate and also express CD5, one that is a subset of pDC (48) and the other referred to as "AS DCs," expressing Axl and Siglec6 (49). The latter were able to transition toward the CD1c + DC state in vitro with superior capacity to activate T cells; however, the authors claim that these cells are less likely to be progenitors.…”
Section: Cd1cmentioning
confidence: 99%